The assessment of heavy rail-based public transportation performances under national key results area (NKRA) 2011-2012 : the case of KTM Komuter - Ummi Aqilah Khalid (Kuliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2016)
Understanding the levels of users' satisfaction across public transport modes is important to encourage more users to choose public transportation over the use of automobiles. This study describes the assessment of users' satisfaction on the service performance of KTM Komuter, focusing on train frequency, delay and capacity. A mix method of quantitative and qualitative methods (onboard intercept questionnaire survey, interviews and minutes of meetings) were adopted for data collection. The KTM Komuter services have long been plagued with issues of punctuality and delay caused by inadequate supply of rolling stocks. Hence, the implementations of NKRA initiatives in the years 2011-2012 were expected to have had positive impacts towards the train's performance. The study recorded that 88% of respondents were experienced users but only 9% were regular commuters (daily commuters). Cross-tabulation and Kendall's correlation analyses were used to identify the relationship and correlation between the socioeconomic and trip characteristics of respondents with their satisfactions towards KTM Komuter services. The results show that increases in users' satisfaction levels were related to increases in the frequency of using the train over the span of a week (travel 7 times a week, 62% felt satisfied); the conveying of information about delays through public announcements (67% felt satisfied) and the provision of an information display board (63% felt satisfied); adequate chances to board the train during peak hours (68% felt satisfied); minimal waiting time for the next train during peak hours (less than 15 minutes waiting time, 67% felt satisfied); minimal waiting time for the next train; and the number of trains abandoned during peak hours (smaller number of waiting trains showed higher occurrences of satisfaction 69%). In contrast, decreases in users' satisfaction were related to increases in the frequency of experiencing delays (17% dissatisfied); and average waiting time during delays on weekdays and weekends (where there was more than 31 minutes in waiting time, 54% felt dissatisfied).